IMPLEMENTASI KESETARAAN DAN KEADILAN GENDER DALAM KELUARGA - Rustina, Rustina (Musawa: Journal for Gender Studies, 2017)
Implementation of gender equality and justice in the family is the functioning of a good family order as an absolute prerequisite for the survival of a new generation of values and norms in accordance with the expectations of society, the realization of mutual understanding of the role of each in the family is characterized by the absence of discrimination between women and men, and thus they have access, opportunity to participate, and control over development and equitable and fair benefits in all sectors of development.